Using 3D animation for learning English: part of human body / Tengku Farhana Tengku Mohd Yusoff - Tengku Mohd Yusoff, Tengku Farhana (2004)
Learning English at the first time is hard because it is not our mother-tongue conversation. Usually, it is difficult to make students especially year 1 to learn because at the early age they are more interesting to play game or something that can give them 'fun'. This project is about the development of 3 dimensions animation in making a English learning. The project's title is Using 3D Animation for Learning English: Part of Human Body. This prototype shows on how computer can make learning become easier and interesting. This thesis wills emphasis more on modeling, animate and rendering as the main methods used to produce the 3D animation. The development of this project follows the Multimedia Development Process Flow as creating a multimedia project can be extremely complex, costly, and time-consuming. In developing this prototype, some software has been used to make it success. Software such as Poser 5.0, Macromedia Director MX, Sound Forge are some of the few to be named. Besides that, there are several benefits while doing this project. This can be one of the methods in supporting the user to learn English as well as learning to interact with computers. This project can be as an alternative to parents who wanted to teach as well as communicating with their children and with the combination of animation, audio, video and graphic, it make this prototype more interesting to learn. Thus, this project can be use as a reference for future generation. It is not only intended for entertainment purposes but is also hope to be a better way in promoting the usage of computers to children. At the end as a conclusion, this thesis will list the limitations on developing the 3D animation.